Designing an RME-Based Hypothetical Learning Trajectory to Enhance Mathematical Communication in Elementary Students - Situs Indrawati; Jesi Alim; Muhammad Fendrik (Universitas Pendidikan Ganesha, 2025)
This research departs from the problem of low student understanding and weak mathematical communication skills in data processing materials at the elementary school level, which are generally caused by abstract learning methods and limitations of contextual teaching materials. The purpose of this research is to design and develop a Hypothetical Learning Trajectory (HLT) based on Realistic Mathematics Education (RME) to improve students' mathematical communication skills through meaningful and contextual learning. This research uses the Plomp development model which consists of three stages, namely the preliminary research stage, the prototyping phase, and the assessment phase. The subjects of the study were elementary school grade VI students and teachers involved in the evaluation process. Data collection techniques were carried out through observation, documentation, interviews, expert validation questionnaires, and practical response questionnaires. The data was analyzed descriptively quantitatively to determine the level of validity and practicality of the developed product. The results of the study showed that the design of RME-based HLT and its supporting devices for teacher books and student books obtained a very valid and very practical category, with a high overall validity score and a high level of practicality. These findings show that the RME-based HLT developed is effective in supporting the improvement of students' mathematical communication skills and can be used as a model for the development of other contextual mathematics teaching materials.